Taking advantage from the EU financial services action plan - recommendations for the Polish stock market - Nawrot, Wioletta (Uniwersytet Ekonomiczny we Wrocławiu, 2008)
After the entry of Poland to the European Union the new legislative environment based on the Financial Services Action Plan brings powerful opportunities to the Polish stock market and its participants. For taking full advantage of them, the Warsaw Stock Exchange must engage fully in the integration process. It is also extremely important to develop and implement policies that act at the macro-economic level to stimulate positive functioning of the capital markets in Poland. On the other hand, Polish companies need to start preparing for the strategic implications of a more integrated financial services market. They will need to ensure their business practices and systems are compliant with the new rules
Argumenta Oeconomica, 2008, No 1 (20), s. 45-66
Keywords: capital markets; European integration; Financial Services Action Plan